2010
DOI: 10.1111/j.1750-3841.2010.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes and Functional Properties of Threadfin Bream Sarcoplasmic Proteins Subjected to pH‐Shifting Treatments and Lyophilization

Abstract: Structural changes and functional properties of threadfin bream (Nemipterus sp.) sarcoplasmic proteins (TB-SP) subjected to various pH conditions (pH 3, 5, 6.3, 9, and 12) after subsequent pH readjustment to pH 7 were investigated. Fourier transform infrared spectroscopy revealed the loss of alpha-helical and beta-sheet structures of TB-SP after being subjected to pH 3 or pH 12 treatments. The extent of structural and conformational changes of TB-SP subjected to pH 3 was greater than alkaline pHs (pH 9, 12) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…There existed about 9 major sarcoplasmic protein bonds with molecular weight that ranged from 14 to 97 kDa, one band had a molecular weight of approximately 14 kDa, 3 of 25 to 31 kDa, and 2 each of 31 to 43 kDa, 50, 60, and 97 kDa (Figure ). The bonds with molecular weight of 41, 39, and 36 kDa from sarcoplasmic proteins represented creatine kinase, aldolase, and glyceraldehyde‐3‐phosphate dehydrogenase, respectively (Yongsawatdigul and Hemung ). A 94 kDa band was assumed to be phosphorylase (Toyohara and others ).…”
Section: Resultsmentioning
confidence: 99%
“…There existed about 9 major sarcoplasmic protein bonds with molecular weight that ranged from 14 to 97 kDa, one band had a molecular weight of approximately 14 kDa, 3 of 25 to 31 kDa, and 2 each of 31 to 43 kDa, 50, 60, and 97 kDa (Figure ). The bonds with molecular weight of 41, 39, and 36 kDa from sarcoplasmic proteins represented creatine kinase, aldolase, and glyceraldehyde‐3‐phosphate dehydrogenase, respectively (Yongsawatdigul and Hemung ). A 94 kDa band was assumed to be phosphorylase (Toyohara and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Alizadeh-Pasdar and Li-Chan (2000) indicated that a decrease of a-helix and an increase in random coil structure of b-lactoglobulin were observed when the pH increased from pH 5 to 9. A drastic loss of a-helical and b-sheet structures of TBSP subjected to extreme alkaline at pH 12 before neutralizing back to pH 7 was previously observed (Yongsawatdigul & Hemung, 2010). It can be noticed that So PRODAN of TBSP at pH 3 was lowest although unfolding would be likely to occur.…”
Section: Effect Of Ph On So Prodanmentioning
confidence: 62%
“…A striking functional property of TBSP was the ability to form a gel-like emulsion containing oil volume fraction of 0.5 at concentration as low as 2 mg/mL without thermal treatment (Yongsawatdigul & Hemung, 2010). The gel-like emulsion has been previously reported in emulsion containing oil volume fraction of 0.75, which was stabilized by crayfish flour at high pH of 11.5 (Romero, Cordobes, Puppo, Cuerrero, & Bengoechea, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this value was increased with the addition of pH‐treated SP samples, and addition of acid‐treated SP had higher shear stress than the alkaline‐treated SP. This study was also agreed with the study of Yongsawatdigul and Hemung (), who reported that the ability of fish SP powder to hold water could be improved by acid and alkaline treatments. In addition, an acid treatment (showing higher degree of denaturation) was more effective to hold water than that of alkaline (Yongsawatdigul & Hemung, ).…”
Section: Resultsmentioning
confidence: 97%